Analysis of selected lymphocyte (CD45+) subset distribution in capillary blood of young soccer players - Nowak, R.; Kostrzewa-Nowak, D.; Buryta, R. (The Journal of Strength and Conditioning Research, 2021)
Mechanisms responsible for increasing athletes' physical capacity and induction of exercise-induced immunosuppression processes are not fully understood. The aim of the study was to monitor changes in percentages of lymphocyte subsets: T, Th, Tc, B, and NK cells in capillary blood of junior soccer players. Ten subjects median aged 18 years (range 17-19 years) were recruited form young soccer players. Capillary blood was collected 24 hours after each soccer match during the 8 weeks of the final phase of Central Junior League competition, and white blood cell (WBC) phenotyping was performed to determine the percentages of B lymphocytes, NK cells, and T-lymphocyte subsets. Cumulative match-time (a sum of time spend playing the game by each athlete during the observation period) was also calculated. Significant changes in the percentage of total lymphocytes (p = 0.00005) and T cells (p = 0.00006) were observed. The slight increases in lymphocytes' and Th cells' median percentages correlated with increasing cumulative match-time of studied subjects, although the correlation was not strong (R = 0.24; p = 0.0205 and R = 0.30; p = 0.0035, for lymphocytes and Th cells, respectively). It seems that the exercise bouts are among considerable factors influencing the changes in WBC subsets, especially in CD3+ cells, among young soccer players. Regarding the number of games played and training loads, they are more susceptible to immunosuppression and subsequent infections and thus should be monitored regarding WBC phenotype assessment.